Association between green tea and coffee consumption and body iron storage in Japanese men and women: a cross-sectional study from the J-MICC Study Saga - Nanri, Hinako; Hara, Megumi; Nishida, Yuichiro; Shimanoe, Chisato; Iwasaka, Chiharu; Higaki, Yasuki; Tanaka, Keitaro (Frontiers in Nutrition, 2023)
This study examined the association between daily green tea and coffee consumption and body iron stores among Japanese middle-aged and older adults. This cross-sectional study used data obtained from 2005 to 2007. A total of 10,435 participants were recruited for this study. The participants completed a validated, self-administered food frequency questionnaire on green tea and coffee consumption. A multivariate linear regression analysis was conducted to assess the relationship between green tea and coffee consumption and serum ferritin levels. Additionally, logistic regression analysis was performed to ascertain whether excessive consumption of these beverages was linked to iron deficiency. We observed that higher green tea and coffee consumption was associated with lower ferritin levels in men and postmenopausal women, even after adjusting for covariates (all P for trends < 0.05). Among premenopausal women, we found an inverse association between green tea consumption and serum ferritin levels, while no significant association was observed for coffee consumption after adjusting for covariates (green tea, P for trend <0.05; coffee, P for trend = 0.08). Notably, the association between these beverages and iron deficiency was found only in postmenopausal women; the odds ratios (95% confidence intervals) for iron deficiency associated with almost None, <1 cup/day, 1-2 cups/day, and ≥3 cups/day were 1.00 (reference), 0.78 (0.26-2.49), 1.29 (0.49-3.39), and 1.59 (0.63-4.04) (P for trend = 0.05), respectively, for green tea and 1.00, 1.32 (0.64-2.73), 1.46 (0.68-3.13), and 2.20 (1.06-4.55) (P for trend <0.01), respectively, for coffee. Higher green tea and coffee consumption was associated with lower serum ferritin levels in men and postmenopausal women. In premenopausal women, consumption of green tea, but not coffee, was associated with lower serum ferritin levels. However, postmenopausal women who ≥3 cups of coffee demonstrated a higher prevalence of iron 4 deficiency compared to those who consumed almost none.